The Effects of Securities Class Action Litigation on Corporate Liquidity and Investment Policy - Arena, Matteo; Julio, Brandon (Journal of Financial and Quantitative Analysis, 2015)
Abstract The risk of securities class action litigation alters corporate savings and investment policy. Firms with greater exposure to securities litigation hold significantly more cash in anticipation of future settlements and other related costs. The result is due to firms accumulating cash in anticipation of lawsuits and not a consequence of plaintiffs targeting firms with high cash levels. The market value of cash is lower for firms exposed to litigation risk. Corporate investment decisions are also affected by litigation risk, as firms reduce capital expenditures in response. Our results are robust to endogeneity concerns and possible spurious temporal effects.